2022
DOI: 10.1039/d2sc00326k
|View full text |Cite
|
Sign up to set email alerts
|

A two-photon ratiometric fluorescent probe for real-time imaging and quantification of NO in neural stem cells during activation regulation

Abstract: Developing a novel tool capable of real-time monitoring and accurate quantification of NO is critical to understanding its role in physiological and pathological processes. Herein, a two-photon ratiometric fluorescent probe...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 45 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…48,49 The sharp peaks at 1684 cm À1 and 1490 cm À1 are in accord with the CQO stretching and N-H bending. 50 However, the FT-IR spectrum also confirmed that the Q[6]-CDs contains functional groups of ÀOH (3092 cm À1 ) and CQO (1705 cm À1 ), 51 and -C-N (1400 cm À1 ), -C-O and -C-O-C (1000-1200 cm À1 ), 52 -COOH (1050 cm À1 ) were present. New absorption bands belonging to the stretching vibration of -C-H (2867 cm À1 , 2951 cm À1 ) in the Q[6]-CDs, 53 and the stretching vibrations of C-F bond at 1249 cm À1 were observed 54 (Fig.…”
Section: Characterization Of Q[6]-cdsmentioning
confidence: 91%
“…48,49 The sharp peaks at 1684 cm À1 and 1490 cm À1 are in accord with the CQO stretching and N-H bending. 50 However, the FT-IR spectrum also confirmed that the Q[6]-CDs contains functional groups of ÀOH (3092 cm À1 ) and CQO (1705 cm À1 ), 51 and -C-N (1400 cm À1 ), -C-O and -C-O-C (1000-1200 cm À1 ), 52 -COOH (1050 cm À1 ) were present. New absorption bands belonging to the stretching vibration of -C-H (2867 cm À1 , 2951 cm À1 ) in the Q[6]-CDs, 53 and the stretching vibrations of C-F bond at 1249 cm À1 were observed 54 (Fig.…”
Section: Characterization Of Q[6]-cdsmentioning
confidence: 91%
“…Some reactive small molecules like nitrogen monoxide (NO) still need a special strategy (e.g., detect NO 2 À , NO 3 À instead of NO) or use small molecule-based probes. [312][313][314][315] Normally, the DNA sequences encoding these sensors are programmed onto the sequence of adeno-associated virus (AAV), transfected into cells for screening and optimisation, and injected into animal brains several weeks before imaging. Although the transmembrane topology may make the fusion protein difficult to travel to the proper location, the high selectivity, affinity, and rich natural diversity give rise to the design of sensors of highly specific properties and applications.…”
Section: Neurotransmitter Sensorsmentioning
confidence: 99%
“…Fluorescence imaging has fascinated increasing regard in the field of brain imaging due to its advantages of non-radiotoxicity, non-invasiveness, high spatiotemporal resolution, rapid detection and high sensitivity [365][366][367][368][369]. With the mastery of the synthesis of fluorescent reagents and the vigorous expansion of optical technologies, fluorescence imaging technology has developed dramatically, realizing the identification and detection of brain regions [370][371][372][373][374]. The imaging resolution can reach single nanometer level, and the imaging depth in several millimeters can even be achieved.…”
Section: The Development Of Multiple Chemical Fluorescent and Raman M...mentioning
confidence: 99%